2022
DOI: 10.47371/mycosci.2022.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Mushroom poisoning in Thailand between 2003 and 2017

Abstract: Mushroom poisoning is an important food-borne disease causing a problem for public health in many countries. Reports from various countries have been published, such as Japan (Ishihara &

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…This difference is probably attributable to the different rainfall, in fact in 2017 the precipitation levels were significantly lower compared to the other years (data not shown). Similar fluctuations generally attributable to climatic conditions have been highlighted by other authors (Cervellin et al., 2018 ; Keller et al., 2018 ; Somrithipol et al., 2022 ).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…This difference is probably attributable to the different rainfall, in fact in 2017 the precipitation levels were significantly lower compared to the other years (data not shown). Similar fluctuations generally attributable to climatic conditions have been highlighted by other authors (Cervellin et al., 2018 ; Keller et al., 2018 ; Somrithipol et al., 2022 ).…”
Section: Resultssupporting
confidence: 84%
“…Overall, 92 (56.1%) intoxicated were males, and 72 (43.9%) females. Epidemiological inequality in gender has been reported by several studies from Thailand (Somrithipol et al, 2022), Anatolia (Cevik & Unluoglu, 2014), and Switzerland (Keller et al, 2018) where MP was more frequent in females, whereas others showed a higher number of male patients, in agreement with our findings (Jiang et al, 2018;Kintziger et al, 2011;Lewinsohn et al, 2023).…”
Section: As Indicated Insupporting
confidence: 93%
See 2 more Smart Citations
“…In Germany, from 2000 to 2018, 4441 patients received hospital treatments due to the consumption of toxic mushrooms, resulting in 22 fatalities (Wennig et al 2020 ). Additionally, Thailand reported 22,571 cases of mushroom poisoning and 106 associated deaths between 2003 and 2017 (Somrithipol et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%